Humoral response induced after intranasal vaccination with heat inactivated Acinetobacter baumannii protects immunodeficient mice against hypervirulent LAC-4 strain - Rouma, Thomas; Barbieux, Emeline; Bossi, Lorenzo; Poncin, Katy; Denanglaire, Sébastien; Tafesse, Yohannes; Vermijlen, David; Delbauve, Sandrine; Flamand, Véronique; Van Buylaere, Juliette; Van der Henst, Charles; De Bolle, Xavier; et al. (Frontiers in Immunology, 2025)
BackgroundAcinetobacter baumannii is an opportunistic bacterium that causes serious nosocomial infections, including pneumonia and bacteremia, especially in immunocompromised individuals.MethodsHere, we first evaluated the protective efficacy of a vaccination protocol with the heat-killed (HK) A. baumannii strain LAC-4 in various models of immunodeficient C57BL/6 mice challenged with pulmonary infection by LAC-4. We then examined the ability of HK LAC-4 to stimulate peripheral blood mononuclear cells (PBMCs) from healthy donors in vitro.ResultsWe observed that mice deficient in Th1 (IL-12p35-/-, IFN-γ-/-), Th17 (IL-17RA-/-) and T cells (δTCR-/-, TAP1-/-, CD3-/-) display higher susceptibility to LAC-4 infection, but that our protocol improves their resistance. In contrast, vaccinated B cell-deficient (MuMT-/-) mice appear unable to control the infection, demonstrating that humoral immunity is essential to vaccine protection. Vaccination of wild-type mice with an HK ΔitrA strain deficient for capsule production failed to induce protection, showing that protective antibodies are mainly directed against the capsule. Our vaccination protocol also confers increased protection in wild-type mice vaccinated and then treated with cyclophosphamide; an immunosuppressive drug described to strongly increase the susceptibility of mice to A. baumannii infection. Finally, we demonstrate that HK LAC-4 can induce the activation of human monocyte-derived dendritic cells and T lymphocytes from PBMCs of healthy donors, suggesting that it may activate the human adaptive immune system and induce a protective memory response against A. baumannii.ConclusionsOverall, our results demonstrate that administration of HK bacteria can induce protective immunity against A. baumannii in both immuno-competent and immuno-compromised mice and that these HK bacteria can activate the human adaptive immune system.